THE COMPARISON OF TEAM ASSISTED INDIVIDUALIZATION AND THINK PAIR SHARE WITH GUIDED NOTE TAKING ON RELATION AND FUNCTION VIEWED FROM ADVERSITY QUOTIENT STUDENT - Rizky Anggar Kusuma Wardani; Mardiyana Mardiyana; Dewi Retno Sari Saputro (Proceedings Education and Language International Conference, 2017)
The research was a quasi-experimental research with a factorial design 2 x 3 aims to determine the comparison of Team Assisted Individualization – Guided Note Taking (TAI-GNT) and Think Pair Share - Guided Note Taking (TPS-GNT) viewed from Adversity Quotient for students’ mathematics achievement. The population of this research were all of Junior High School Students 8th grade in Magetan Regency schools in academic year 2016/2017 whom applied KTSP curriculum. The sampling techniques was taken by using stratified cluster random sampling. The data was collected by using methods of documentation, questionnaires on students AQ, and mathematics achievement test. The analysis data technique used two-ways analysis of variance with unbalanced cells, with significance level was 0.05. Based on the study result, it could be concluded that : (1) TAI-GNT learning model made better mathematics learning achievement than TPS-GNT learning model, (2) Climber students got better mathematics learning achievement than Camper students and Quitter students, while Camper students got better mathematics learning achievement than Quitter students, (3) for every learning model, climber student got better mathematic learning achievement than Camper students and Quitter students, while Camper student got better mathematic learning achievement than Quitter student, (4) for every categories AQ, TAI-GNT learning model made better mathematics learning achievement than TPS-GNT learning model.Keywords: Adversity Quotient (AQ), Guided Note Taking (GNT), Mathematics Learning Achievement, Relation and Function, Team Assisted Individualization (TAI), Think Pair Share (TPS)